Social Interaction Among the Elderly During the Covid-19 Pandemic in Central Jakarta - Debora Tamo Inya; Santa Maria Pangaribuan; Sri Hunun Widiastuti (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: The impact of Covid-19 is beyond the interpretation of various groups in Indonesia, Covid-19 has a worrying and detrimental impact on various aspects of society. The conditions that have an impact are seen in changes in interaction, where due to the government's policy to carry out physical distancing, and quarantine, social interaction between communities’ decreases, as a result, there is a community structure that causes a shift in lifestyle to new habits that make social interaction erosion in the community, especially among the elderly. The purpose of this study is to find out about social interactions among the elderly during the Covid-19 pandemic in Cempaka Putih, Central Jakarta. Method: The research design used is a quantitative descriptive method using univariate analysis. The questionnaire consists of 12 question items, where the questionnaire used has been declared valid and reliable. The sample used in this study was 108 respondents. Results: The results of this study were that there were 100 elderly or 92.6% of the elderly who had sufficient social interaction. Discussion: This study possesses that most of the elderly have sufficient social interaction, so it is expected for the local health service to run the elderly program with Group Activity Therapy during the pandemic by complying with health protocols.